2018
DOI: 10.1007/s40261-018-0660-2
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Rising Doses of Oral BI 425809, a GlyT1 Inhibitor, in Young and Elderly Healthy Volunteers: A Randomised, Double-Blind, Phase I Study Investigating Safety and Pharmacokinetics

Abstract: Background and ObjectiveSchizophrenia and Alzheimer’s disease are characterised by abnormalities in glutamatergic pathways related to N-methyl-d-aspartate receptor hypofunction. Glycine is an N-methyl-d-aspartate receptor co-agonist; inhibition of glycine transporter 1 may improve N-methyl-d-aspartate receptor function. This phase I, randomised, two-part study evaluated the safety, tolerability and pharmacokinetic profile of BI 425809, a novel glycine transporter 1 inhibitor, in healthy male and female volunte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 18 publications
1
20
0
Order By: Relevance
“…BI 425809 is a novel potent and selective GlyT1 inhibitor being developed for the treatment of cognitive impairment associated with schizophrenia and AD . It has previously been observed that the half‐life value of BI 425809 is ~40 hours, consistent with attainment of steady state within 8 days after administration . The objective of the preclinical study described here was to characterize the potency and selectivity of BI 425809, and its effects on glycine concentration in rat cerebrospinal fluid (CSF).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…BI 425809 is a novel potent and selective GlyT1 inhibitor being developed for the treatment of cognitive impairment associated with schizophrenia and AD . It has previously been observed that the half‐life value of BI 425809 is ~40 hours, consistent with attainment of steady state within 8 days after administration . The objective of the preclinical study described here was to characterize the potency and selectivity of BI 425809, and its effects on glycine concentration in rat cerebrospinal fluid (CSF).…”
mentioning
confidence: 99%
“…6,7 It has previously been observed that the half-life value of BI 425809 is ~40 hours, consistent with attainment of steady state within 8 days after administration. 6,8 The objective of the preclinical study described here was to characterize the potency and selectivity of BI 425809, and its effects on glycine concentration in rat cerebrospinal fluid (CSF). To translate this preclinical study into humans, BI 425809 was further evaluated in a phase I study with healthy volunteers.…”
mentioning
confidence: 99%
“…Furthermore, BI 425809 was recently developed by Boehringer Ingelheim as a novel, investigational GlyT1 inhibitor to improve cognitive function and memory in patients with schizophrenia and Alzheimer's disease (224)(225)(226). A recent randomized doubleblind, placebo-controlled phase II study revealed that BI 425809 improved cognitive functions after 12 weeks in patients with schizophrenia (215), suggesting that BI 425809 can provide an effective treatment for cognitive impairment associated with schizophrenia.…”
Section: Non-sarcosine-based Glyt1 Inhibitorsmentioning
confidence: 99%
“…Glycine is an obligatory co-agonist for NMDA receptor activation; inhibitors of synaptic glycine uptake are therefore thought to enhance NMDA receptor signaling [29] and may promote downstream plasticity processes [30]. BI 425809 is generally well tolerated in healthy volunteers, and the most commonly reported adverse events (AEs) in Phase I studies included headache, back pain, nausea, vomiting, and neck pain [31,32]. A Phase II clinical proof-of-concept and dose-finding study investigating the potential benefits of BI 425809 as add-on therapy to standard of care for CIAS in patients with schizophrenia is currently underway (NCT02832037).…”
Section: Key Pointsmentioning
confidence: 99%